**prime number**can be expressed as $a^2 + 2 b^2$, then show that the prime number can be written as $x^2 + 2 y^2$.

## #Number Theory

- Kazi_Zareer
**Posts:**86**Joined:**Thu Aug 20, 2015 7:11 pm**Location:**Malibagh,Dhaka-1217

### #Number Theory

If the square of any

Last edited by Masum on Sat Oct 10, 2015 12:21 am, edited 1 time in total.

**Reason:***Put dollars between math expressions*### Re: #Number Theory

See the article here.

viewtopic.php?f=26&t=3422

viewtopic.php?f=26&t=3422

One one thing is neutral in the universe, that is $0$.

### Re: #Number Theory

Your claim does not hold if $b=0$ so I'll assume that $ab\neq 0$. Then $p$ must be odd.

Suppose that $p^2=a^2+2b^2$. Then $(p+a)(p-a)=2b^2$, so $p\pm a$ are both even. Set $p+a=2x$ and $p-a=2y$. Then $2xy=b^2$, implying that $b$ is even. Set $b=2z$. Then $xy=2z^2$.

Note that $(x,y)$ divides $2p$ and $2a$, hence $2(p,a)$. Since $p$ cannot divide $a$, $(p,a)=1$, i.e., $(x,y)=1$ or $2$. If $(x,y)=2$ then $4$ divides $p\pm a$, and so $4$ divides $2p$, which is impossible.

Hence $(x,y)=1$. Since $2\mid xy$, it follows that $2\mid x$ or $2\mid y$. If $x=2x'$ then $x'y=z^2$ with $(x',y)=1$. Hence $x'=u^2$, $y=v^2$ for some integers $u,v$. This implies $x=2u^2$, $y=v^2$ and thus $p+a=4u^2$, $p-a=2v^2$. Solving for $p$ yields $p=v^2+2u^2$, as desired. If $y=2y'$ one obtains a similar conclusion.

Suppose that $p^2=a^2+2b^2$. Then $(p+a)(p-a)=2b^2$, so $p\pm a$ are both even. Set $p+a=2x$ and $p-a=2y$. Then $2xy=b^2$, implying that $b$ is even. Set $b=2z$. Then $xy=2z^2$.

Note that $(x,y)$ divides $2p$ and $2a$, hence $2(p,a)$. Since $p$ cannot divide $a$, $(p,a)=1$, i.e., $(x,y)=1$ or $2$. If $(x,y)=2$ then $4$ divides $p\pm a$, and so $4$ divides $2p$, which is impossible.

Hence $(x,y)=1$. Since $2\mid xy$, it follows that $2\mid x$ or $2\mid y$. If $x=2x'$ then $x'y=z^2$ with $(x',y)=1$. Hence $x'=u^2$, $y=v^2$ for some integers $u,v$. This implies $x=2u^2$, $y=v^2$ and thus $p+a=4u^2$, $p-a=2v^2$. Solving for $p$ yields $p=v^2+2u^2$, as desired. If $y=2y'$ one obtains a similar conclusion.

"Everything should be made as simple as possible, but not simpler." - Albert Einstein